Gaelic dialects present and past: a study of modern and medieval dialect relationships in the Gaelic languages - O' Muircheartaigh, Peadar (The University of Edinburgh, 2015)
This thesis focuses on the historical development of dialectal variation in the Gaelic languages with special reference to Irish. As a point of departure, competing scholarly theories concerning the historical relationships between Goidelic dialects are laid out. Next, these theories are tested using dialectometric methods of linguistic analysis. Dialectometry clearly suggests the Irish of Ulster is the most linguistically distinctive of Irish dialects. This perspective on the modern dialects is utilised in subsequent chapters to clarify our understanding of the history of Gaelic dialectal variation, especially during the Old Irish period (AD 600–900). Theoretical and methodological frameworks that have been used in the study of the historical dialectology of Gaelic are next outlined. It is argued that these frameworks may not be the most appropriate for investigating dialectal variation during the Old Irish period. For the first time, principles from historical sociolinguistics are here applied in investigating the language of the Old Irish period. In particular, the social and institutional structures which supported the stability of Old Irish as a text language during the 8th and 9th centuries are scrutinised from this perspective. The role of the ecclesiastical and political centre of Armagh as the principal and central actor in the relevant network structures is highlighted. Focus then shifts to the processes through which ‘standard’ languages emerge, with special reference to Old Irish. The evidence of a small number of texts upon which modern understandings of Old Irish was based is assessed; it is argued that these texts most likely emerged from monasteries in the northeast of Ireland and the southwest of Scotland. Secondly, the processes through which the standard of the Old Irish period is likely to have come about are investigated. It is concluded that the standard language of the period arose primarily through the agency of monastic schools in the northeast of Ireland, particularly Armagh and Bangor. It is argued that this fact, and the subsequent prominence of Armagh as a stable and supremely prestigious centre of learning throughout the period, offers a sociolinguistically robust explanation for the apparent lack of dialectal variation in the language. Finally, the socio-political situation of the Old Irish period is discussed. Models of new-dialect formation are applied to historical evidence, and combined with later linguistic evidence, in an attempt to enunciate dialectal divisions which may have existed during the period.
Keywords: gaelic lanuages; dialectal variation; Old Irish; new-dialect formation